A quick guide to welding and weld inspection - Hughes, Steven E. (Engineer) (Quick guide (Cambridge, England), 2009)
"A Quick Guide to Welding and Weld Inspection is a simple guide to the knowledge required to fulfill the role of a welding inspector. In covering both European and US-based codes, the book will give those wishing to gain certification in welding inspection a basic all-round understanding of the main subject matter." "This book describes welding terminology, abbreviations and symbols. The duties of a welding inspector are discussed. Materials and their weldability, welding processes and welding defects are all covered, with additional supporting documentation on codes and standards."--Jacket.